2012
DOI: 10.2106/jbjs.j.01134
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Contralateral Proximal Femoral Fracture Following Closed Reduction and Percutaneous Pinning Compared with Arthroplasty for the Treatment of Femoral Neck Fractures

Abstract: Patients undergoing closed reduction and percutaneous pinning as the initial treatment for a hip fracture had an increased risk of a subsequent contralateral hip fracture in comparison with those undergoing arthroplasty, after controlling for patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…With this elderly population increase, the rate of hip fractures is expected to increase from less than 2 million in 1990 to more than 6 million by 2050 [28]. The increasing yearly prevalence and morbidity and mortality associated with FNFs have led to extensive research and multiple publications on which to base treatment decisions [1,4,5,9,19,25,26,31,33,36,38,42,45,[47][48][49]51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this elderly population increase, the rate of hip fractures is expected to increase from less than 2 million in 1990 to more than 6 million by 2050 [28]. The increasing yearly prevalence and morbidity and mortality associated with FNFs have led to extensive research and multiple publications on which to base treatment decisions [1,4,5,9,19,25,26,31,33,36,38,42,45,[47][48][49]51].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality at 1 year ranges from 14% to 36% but without differences in mortality between fixation and hemiarthroplasty at 1, 5, and 10 years [8,18,19,31,36,37]. Fixation is associated with higher risk of contralateral hip fracture than arthroplasty [48]. Despite the growing amount of research on this subject, no clinical consensus exists regarding how to best treat FNFs with the primary intention of avoiding reoperation in an effort to avoid additional risks to these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Th e purpose of this study was to report the rate of contralateral hip fracture after an initial IT/PT fracture treated with HSSP compared with CMN. One might expect this study to produce outcomes similar to those of Souder et al (12), especially with the large number of patients and a similar database of patients. However, our results indicated no diff erence in the rate of contralateral hip fractures when treating IT/PT proximal femur fractures with HSSP compared with CMN.…”
Section: Discussionmentioning
confidence: 54%
“…Souder et al (12) recently reported a signifi cantly increased risk of subsequent contralateral hip fracture after treatment of a femoral neck fracture with closed reduction percutaneous pinning in comparison with hip arthroplasty. Th e purpose of this study was to report the rate of contralateral hip fracture after an initial IT/PT fracture treated with HSSP compared with CMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation